OPTIMASI RUTE PENYEBARAN BROSUR BIMBINGAN BELAJAR MENGGUNAKAN ALGORITMA GENETIKA - M.Irfan Hanafi; Billy Coster Junior; Yesy Diah Rosita (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Brand Brilliant College (BBC) tutoring is one of the tutoring places in Kutorejo District, Mojokerto Regency which has teaching and learning activities between students and tutors. In Kutorejo District there are many schools of various levels of education, one of which is Elementary School. In this regard, the purpose of this research is to find the optimal route for travel in brochure distribution activities which is very necessary in order to obtain the effectiveness of the minimum distance. In this case, CSR theory is one of the solutions to problems in planning. the method used for TSP is Genetic Algorithm with data clustering using k-means. The location of tutoring is represented by a directed line. With several trials using the Genetic Algorithm produced 3 optimal routes, namely 1 1-8-6-7-5-4-2, 2.1-3-5-7-8-4-6-9-2 and 3.1-8-7 -11-9-12-5-4-2-3-6-10 with a total distance of 46.7972 KM with this test can produce an optimization route for the journey of BBC tutoring staff to elementary schools in Kutorejo District, Mojokerto Regency